Filamentous hemagglutinin of Bordetella pertussis: a key adhesin with immunomodulatory properties?. (December 2014) - Villarino Romero, Rodrigo; Osicka, Radim; Sebo, Peter
ABSTRACT : The filamentous hemagglutinin of pathogenic Bordetellae is a prototype of a large two-partner-system-secreted and β-structure-rich bacterial adhesin. It exhibits several binding activities that may facilitate bacterial adherence to airway mucosa and host phagocytes in the initial phases of infection. Despite three decades of research on filamentous hemagglutinin, there remain many questions on its structure–function relationships, integrin interactions and possible immunomodulatory signaling capacity. Here we review the state of knowledge on this important virulence factor and acellular pertussis vaccine component. Specific emphasis is placed on outstanding questions that are yet to be answered.